Pemberdayaan Masyarakat Bagi Keluarga Pemulung Di Kelurahan Rappokalling Kecamatan Tallo Kota Makassar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study  aimed to find out how to empower the community for scavenger families in Rappokalling Village, Tallo District, Makassar City. The number of informants was 10 people. This study used qualitative with descriptive research type. Data collection techniques were observation, interviews, and documentation. Data analysis used data reduction, data presentation, and data verification. This study used the theory of empowerment aspects of Edi Suharto, with the results showed protection; the scavenger community had never received discrimination from strong community groups. Strengthening: training programs for scavenger communities had been successful in increasing self-reliance and improving socio-economic conditions. Support: providing support, education and motivation to the scavenger community had succeeded in increasing public awareness about the importance of improving socio-economic quality. Maintenance: in this case the maintenance carried out by the scavenger community was considered successful, in ensuring balance and harmony so that every scavenger community had the opportunity to do business. Possibility: that the scavenger succeeded in eliminating the possibilities that could hinder the scavenger community from developing.Keywords: Empowerment, community, scavenger families